Differentiated Assessment Practices in EFL Classrooms: Evidence from a Senior High School in Indonesia - La Sunra; Nur Alya Triana; Baso Jabu (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Assessment plays an essential role in differentiated learning as it provides information about students' readiness, learning progress, and instructional needs. Through assessment, teachers can adjust instruction and learning activities to support diverse learners in the classroom. In English language teaching, assessment is expected to function as an integral part of the learning process rather than merely as a tool for measuring outcomes. This study aims to explore the implementation of differentiated learning assessment in an English as a Foreign Language (EFL) classroom, focusing specifically on diagnostic and formative assessment practices. A qualitative case study design was employed to gain an in-depth understanding of these practices. The study was conducted at SMAN 2 Makassar in October 2025, involving one English teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis. Findings indicate that the teacher implemented diagnostic assessment at the beginning of the semester to identify students' initial abilities and employed continuous formative assessment to monitor learning progress and provide feedback. Key formative practices included real-time corrective feedback, consultation mechanisms during writing tasks, peer and self-assessment activities, and sequentially organized learning activities that supported progressive skill development. Student perceptions, gathered through questionnaires, were generally positive, with the majority appreciating teacher feedback, valuing sequential learning progression, and finding diagnostic assessment helpful for understanding their strengths and weaknesses. However, implementation of differentiated assessment remained limited in certain areas, particularly in task variation, the use of diverse assessment instruments, and systematic attention to students' interests and learning profiles. The study concludes that while principles of assessment for learning have been applied, further professional development is needed to strengthen differentiated assessment practices in responding to students' diverse learning needs, particularly in expanding beyond readiness-based differentiation to address the full spectrum of student characteristics.